Evaluation of Nicotine Dependence in Adult Population of Eastern Nepal - Shrestha, A.; Marla, V.; Lamsal, M.; Sarraf, D. P.; Rao, N. (Kathmandu University Medical Journal, 2021)
Background Tobacco consumption is a leading cause of premature death in the world. Tobacco-related deaths are associated with cardiovascular diseases, pulmonary diseases, oral potentially malignant disorders, cancer, others. Moreover there is also associated nicotine dependence which might result to numerous tobacco-associated diseases. Objective This study was conducted to analyze the degree of nicotine dependence considering its potential health risk, in the Eastern region of Nepal. Method A descriptive questionnaire-based study was conducted among current tobacco users of six districts of Eastern Nepal. Fagerstrom Test for Nicotine Dependence (FTND) and Fagerstrom Test for Nicotine Dependency for Smokeless Tobacco (FTNDST) questionnaire were used for tobacco smokers and chewers, respectively. Result Of the total participants, 836 were males and 359 females, among whom 736 were active tobacco smokers and 432 chewers, 34.8% had tried to stop consuming tobacco and 306 (25.6%) had oral lesions in white or red forms. Very low nicotine dependence was found among 244 (31.47%) tobacco smokers and 37 (8.56%) chewers whereas 36 (4.71%) smokers and 103 (23.84%) chewers had very high nicotine dependence. The mean score for FTND was 3.73±2.37 and 5.74±2.12 for FTND-ST. A significant difference in duration and age group with FTND score was observed, however not with FTND-ST. Conclusion The information regarding degree of nicotine dependence can be used as baseline information for planning of preventive strategies and implementation of tobacco cessation and control programs.